458. Multimodal analgesia after oesophagectomy provides clinically equivalent pain control for open and thoracoscopic approaches. (24th September 2022) - Chung, Jordan Ng Cheong; Barry, James; Chmelo, Jakub; Navidi, Maziar; Phillips, Alexander
Abstract: Adequate pain control is an important consideration to ensure patients can mobilise after surgery and to reduce pulmonary complications. This is frequently provided by a thoracic epidural, however there has been increasing use of multimodal analgesia. Minimally invasive approaches in esophagectomy may also reduce post-operative pain. The aim of this study was to compare pain control in patients after Ivor Lewis esophagectomy with thoracoscopic (TE) vs open approach using multimodal analgesia. Consecutive patients undergoing thoracoscopic or open esophagectomy for cancer between January 2015 and December 2019 were evaluated. All patients received multimodal analgesia (intrathecal diamorphine, paravertebral and rectus sheath catheters). Pain scores (at rest and on movement, graded from 0 to 10) were collected and compared between two cohorts. Length of stay and complications were also compared between the two groups. This study included 161 patients; 114 (70.8%) underwent an open esophagectomy and 47 (29.2%) underwent a thoracoscopic chest phase. Mean pain scores were significantly lower for TE only on postoperative days (POD) 0 on movement (open 2.81 versus TE 1.50, p = 0.026) and POD 3 at rest (open 1.00 versus TE 0.60, p = 0.030). Postoperative stay was comparable between groups (9 versus 8 days). There was no significant difference in the overall complication rate (64.0% versus 57.4%, p = 0.433), pulmonary complications (27.7% versus 35.1% p = 0.461) and 30-day mortality (2.6% versus 0%, p = 0.262). These results may suggest that a minimally invasive thoracoscopic approach does not provide additional analgesic benefit in comparison to open approach when multimodal analgesia is used. A clinically meaningful difference (score difference 0.9-1.6) was achieved only on POD 0. Importantly, in this cohort the open approach was not associated with inferior short-term postoperative outcomes. Future randomised controlled trials comparing minimally invasive techniques should consider employing multimodal analgesia in their design.